TUGAS POKOK SEBAGAI FUNGSI ORGANISASI TERHADAP PENINGKATAN KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MUSI BANYUASIN - Avissa Calista; Ika Rakhmalina (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
This study aims to determine and analyze the effect of basic tasks as an organizational function on improving performance in the Population and Civil Registry Office of Musi Banyuasin Regency. The design of this study intends to reveal the existence of a relationship or influence between the independent variable with the dependent variable. In statistics, the method of analysis that suits these problems is regression analysis, where one dependent variable is influenced by several independent variables. The dependent variable is a variable that is assumed to only appear because of the influence of the independent variable. From the value of t arithmetic above can be seen that t arithmetic 5.321. while t table is known by distribution table with degrees of freedom (df) n-k-1 so it is known that t table is 1.70 then Ho is rejected so it can be seen that the main tasks and functions of the organization affect the performance of employees in the Population and Civil Registry Office of Musi Banyuasin Regency. The level of significance of the variable is known that the variable is significant because the significance value is below 0.05 so it can be said that the main task and function variables (Tupoksi) of the organization can be used to predict employee performance in the Population and Civil Registry Office of Musi Banyuasin Regency (Y). The results of the study both in description and statistics that researchers do note that the independent variable (tupoksi) has an influence on the dependent variable (employee performance at the Population and Civil Registry Office of Musi Banyuasin Regency). This is evidenced from the regression test, correlation test and simultaneous test. From the significance level, it can be seen that all significant variables mean that in this study all independent variables influence the dependent variable